Single Cell Transcriptomic Profiling of Vascular Smooth Muscle Cell Phenotype Modulation in Marfan Syndrome Aortic Aneurysm - Pedroza, Albert J. (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: To delineate temporal and spatial dynamics of vascular smooth muscle (SMC) transcriptomic changes during aortic aneurysm development in Marfan syndrome (MFS). APPROACH AND RESULTS: We performed single-cell RNA sequencing (scRNAseq) to study aortic root/ascending aneurysm tissue from Fbn1(C1041G/+) (MFS) mice and healthy controls, identifying all aortic cell types. A distinct cluster of transcriptomically modulated SMCs (modSMCs) was identified in adult Fbn1(C1041G/+) mouse aortic aneurysm tissue only. Comparison with atherosclerotic aortic data (ApoE(−/−) mice) revealed similar patterns of SMC modulation but identified a MFS-specific gene signature including Serpine1 and Klf4. We identified 481 differentially expressed genes between modSMC and SMC subsets; functional annotation highlighted ECM modulation, collagen synthesis, adhesion and proliferation. Pseudotime trajectory analysis of Fbn1(C1041G/+) SMC/modSMC transcriptomes identified genes activated differentially throughout the course of phenotype modulation. While modSMCs were not present in young Fbn1(C1041G/+) mouse aortas despite small aortic aneurysm, multiple early modSMCs marker genes were enriched, suggesting activation of phenotype modulation. modSMCs were not found in non-dilated adult Fbn1(C1041G/+) descending thoracic aortas. scRNAseq from human MFS aortic root aneurysm tissue confirmed analogous SMC modulation in clinical disease. Enhanced expression of TGF-β-responsive genes correlated with SMC modulation in mouse and human datasets. CONCLUSIONS: Dynamic SMC phenotype modulation promotes ECM substrate modulation and aortic aneurysm progression in MFS. We characterize the disease-specific signature of modulated SMCs and provide temporal, transcriptomic context to the current understanding of the role TGF-β plays in MFS aortopathy. Collectively, scRNAseq implicates TGF-β signaling and Klf4 overexpression as potential upstream drivers of SMC modulation.